2022
DOI: 10.5435/jaaos-d-21-01254
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sustainability in Orthopaedic Surgery

Abstract: Climate change has been increasingly recognized in the healthcare sector over recent years, with global implications in infrastructure, economics, and public health. As a result, a growing field of study examines the role of healthcare in contributing to environmental sustainability. These analyses commonly focus on the environmental impact of the operating room, due to extensive energy and resource utilization in surgery. While much of this literature has arisen from other surgical specialties, several enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…There were 21 editorials with authors from 13 countries; Australia [ 107 111 ], Brazil [ 109 ], Canada [ 112 ], Germany [ 109 ], Greece [ 109 ], India [ 113 , 114 ], New Zealand [ 109 , 115 ], Norway [ 109 , 111 , 114 , 116 ], Pakistan [ 109 ], Sweden [ 109 , 117 , 118 ], Switzerland [ 109 , 119 ], United Kingdom [ 100 , 109 , 117 , 120 122 ] and United States [ 109 , 116 , 123 – 127 ]. There were four narrative reviews, two from the United States [ 128 , 129 ] and one each from India [ 130 ] and the United Kingdom [ 131 ]. Thirty-six (73%) included publications were related to orthopaedic surgery [ 83 104 , 106 , 117 , 120 131 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 21 editorials with authors from 13 countries; Australia [ 107 111 ], Brazil [ 109 ], Canada [ 112 ], Germany [ 109 ], Greece [ 109 ], India [ 113 , 114 ], New Zealand [ 109 , 115 ], Norway [ 109 , 111 , 114 , 116 ], Pakistan [ 109 ], Sweden [ 109 , 117 , 118 ], Switzerland [ 109 , 119 ], United Kingdom [ 100 , 109 , 117 , 120 122 ] and United States [ 109 , 116 , 123 – 127 ]. There were four narrative reviews, two from the United States [ 128 , 129 ] and one each from India [ 130 ] and the United Kingdom [ 131 ]. Thirty-six (73%) included publications were related to orthopaedic surgery [ 83 104 , 106 , 117 , 120 131 ].…”
Section: Resultsmentioning
confidence: 99%
“…One narrative review on environmental sustainability in orthopaedic surgery, that identified all seven relevant studies that we included, highlighted a need for high-quality research on best practices for orthopaedic surgery to reduce its carbon footprint [ 129 ] (see Table 1 ). The remaining narrative review explored bioresorbable orthopaedic implants as a sustainable alternative to traditional permanent implants for some orthopaedic surgeries [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“… 12 , 13 The main areas of improvement are the reduction of waste volumes and in the equipment supply chain. 14 , 15 , 16 Surgeons play a primary role in reducing the surgical carbon footprint. 12 , 17 Reducing the number of anchors used during surgery is simple and innovative as well as eco-responsible.…”
Section: Discussionmentioning
confidence: 99%
“…5 Global warming decreases food and water supplies, increases the risk of infectious disease, and contributes to economic disruption. 8 In fact, more than 5 million deaths annually can be attributed to nonoptimal temperatures resulting from climate change. 8,9 Air pollution, heat waves, and wildfires can exacerbate cardiovascular disease, asthma, allergies, and infectious disease transmissibility; and the continued increase in the number and severity of weather events creates a greater demand for trauma and mental health care and disrupts access to surgical care.…”
Section: Why It Mattersmentioning
confidence: 99%
“…8 In fact, more than 5 million deaths annually can be attributed to nonoptimal temperatures resulting from climate change. 8,9 Air pollution, heat waves, and wildfires can exacerbate cardiovascular disease, asthma, allergies, and infectious disease transmissibility; and the continued increase in the number and severity of weather events creates a greater demand for trauma and mental health care and disrupts access to surgical care. 5 Bonnie Weinberg, MSN, RN, CNOR, clinical practice specialist, The Valley Hospital, Ridgewood, NJ, indicated that it is essential for perioperative team members to have an interest in saving the planet.…”
Section: Why It Mattersmentioning
confidence: 99%